Biodiesel production from non-edible Mahogany seed oil by dual step process and study of its oxidation stability (Bangladesh Journal of Scientific and Industrial Research, 2015)
Biodiesel derived from non edible sources is a potential eco-friendly substitute to petroleum fuel. Acid-catalysed esterification was applied to reduce free fatty acid (FFA) content of oil to zero followed by base-catalyzed transesterification to convert esterified product to its mono-esters and glycerol. The major factors affecting the conversion efficiency of these two processes such as amounts of solvent and catalyst, reaction temperature, and reaction time were optimized. The physical properties and heating value of Mahogany Seed Oil (MSO) and MSO diesel are evaluated and compared with that of commercial diesel. FTIR and 1H NMR spectrum of MSO and MSO biodiesel confirmed the conversion of MSO to biodiesel. The oxidation stability of MSO biodiesel oil was also studied. The study affirms the production of biodiesel from MSO as a renewable alternative to the diesel fuel.Bangladesh J. Sci. Ind. Res. 50(2), 77-86, 2015